(* Title: HOL/Analysis/Measure_Space.thy Author: Lawrence C Paulson Author: Johannes Hölzl, TU München Author: Armin Heller, TU München *) section ‹Measure Spaces› theory Measure_Space imports Measurable "HOL-Library.Extended_Nonnegative_Real" begin subsection✐‹tag unimportant› "Relate extended reals and the indicator function" lemma suminf_cmult_indicator: fixes f :: "nat ⇒ ennreal" assumes "disjoint_family A" "x ∈ A i" shows "(∑n. f n * indicator (A n) x) = f i" proof - have **: "⋀n. f n * indicator (A n) x = (if n = i then f n else 0 :: ennreal)" using ‹x ∈ A i› assms unfolding disjoint_family_on_def indicator_def by auto then have "⋀n. (∑j<n. f j * indicator (A j) x) = (if i < n then f i else 0 :: ennreal)" by (auto simp: sum.If_cases) moreover have "(SUP n. if i < n then f i else 0) = (f i :: ennreal)" proof (rule SUP_eqI) fix y :: ennreal assume "⋀n. n ∈ UNIV ⟹ (if i < n then f i else 0) ≤ y" from this[of "Suc i"] show "f i ≤ y" by auto qed (insert assms, simp) ultimately show ?thesis using assms by (subst suminf_eq_SUP) (auto simp: indicator_def) qed lemma suminf_indicator: assumes "disjoint_family A" shows "(∑n. indicator (A n) x :: ennreal) = indicator (⋃i. A i) x" proof cases assume *: "x ∈ (⋃i. A i)" then obtain i where "x ∈ A i" by auto from suminf_cmult_indicator[OF assms(1), OF ‹x ∈ A i›, of "λk. 1"] show ?thesis using * by simp qed simp lemma sum_indicator_disjoint_family: fixes f :: "'d ⇒ 'e::semiring_1" assumes d: "disjoint_family_on A P" and "x ∈ A j" and "finite P" and "j ∈ P" shows "(∑i∈P. f i * indicator (A i) x) = f j" proof - have "P ∩ {i. x ∈ A i} = {j}" using d ‹x ∈ A j› ‹j ∈ P› unfolding disjoint_family_on_def by auto with ‹finite P› show ?thesis by (simp add: indicator_def) qed text ‹ The type for emeasure spaces is already defined in \<^theory>‹HOL-Analysis.Sigma_Algebra›, as it is also used to represent sigma algebras (with an arbitrary emeasure). › subsection✐‹tag unimportant› "Extend binary sets" lemma LIMSEQ_binaryset: assumes f: "f {} = 0" shows "(λn. ∑i<n. f (binaryset A B i)) ⇢ f A + f B" proof - have "(λn. ∑i < Suc (Suc n). f (binaryset A B i)) = (λn. f A + f B)" proof fix n show "(∑i < Suc (Suc n). f (binaryset A B i)) = f A + f B" by (induct n) (auto simp add: binaryset_def f) qed moreover have "... ⇢ f A + f B" by (rule tendsto_const) ultimately have "(λn. ∑i< Suc (Suc n). f (binaryset A B i)) ⇢ f A + f B" by metis hence "(λn. ∑i< n+2. f (binaryset A B i)) ⇢ f A + f B" by simp thus ?thesis by (rule LIMSEQ_offset [where k=2]) qed lemma binaryset_sums: assumes f: "f {} = 0" shows "(λn. f (binaryset A B n)) sums (f A + f B)" by (simp add: sums_def LIMSEQ_binaryset [where f=f, OF f] atLeast0LessThan) lemma suminf_binaryset_eq: fixes f :: "'a set ⇒ 'b::{comm_monoid_add, t2_space}" shows "f {} = 0 ⟹ (∑n. f (binaryset A B n)) = f A + f B" by (metis binaryset_sums sums_unique) subsection✐‹tag unimportant› ‹Properties of a premeasure \<^term>‹μ›› text ‹ The definitions for \<^const>‹positive› and \<^const>‹countably_additive› should be here, by they are necessary to define \<^typ>‹'a measure› in \<^theory>‹HOL-Analysis.Sigma_Algebra›. › definition subadditive where "subadditive M f ⟷ (∀x∈M. ∀y∈M. x ∩ y = {} ⟶ f (x ∪ y) ≤ f x + f y)" lemma subadditiveD: "subadditive M f ⟹ x ∩ y = {} ⟹ x ∈ M ⟹ y ∈ M ⟹ f (x ∪ y) ≤ f x + f y" by (auto simp add: subadditive_def) definition countably_subadditive where "countably_subadditive M f ⟷ (∀A. range A ⊆ M ⟶ disjoint_family A ⟶ (⋃i. A i) ∈ M ⟶ (f (⋃i. A i) ≤ (∑i. f (A i))))" lemma (in ring_of_sets) countably_subadditive_subadditive: fixes f :: "'a set ⇒ ennreal" assumes f: "positive M f" and cs: "countably_subadditive M f" shows "subadditive M f" proof (auto simp add: subadditive_def) fix x y assume x: "x ∈ M" and y: "y ∈ M" and "x ∩ y = {}" hence "disjoint_family (binaryset x y)" by (auto simp add: disjoint_family_on_def binaryset_def) hence "range (binaryset x y) ⊆ M ⟶ (⋃i. binaryset x y i) ∈ M ⟶ f (⋃i. binaryset x y i) ≤ (∑ n. f (binaryset x y n))" using cs by (auto simp add: countably_subadditive_def) hence "{x,y,{}} ⊆ M ⟶ x ∪ y ∈ M ⟶ f (x ∪ y) ≤ (∑ n. f (binaryset x y n))" by (simp add: range_binaryset_eq UN_binaryset_eq) thus "f (x ∪ y) ≤ f x + f y" using f x y by (auto simp add: Un o_def suminf_binaryset_eq positive_def) qed definition additive where "additive M μ ⟷ (∀x∈M. ∀y∈M. x ∩ y = {} ⟶ μ (x ∪ y) = μ x + μ y)" definition increasing where "increasing M μ ⟷ (∀x∈M. ∀y∈M. x ⊆ y ⟶ μ x ≤ μ y)" lemma positiveD1: "positive M f ⟹ f {} = 0" by (auto simp: positive_def) lemma positiveD_empty: "positive M f ⟹ f {} = 0" by (auto simp add: positive_def) lemma additiveD: "additive M f ⟹ x ∩ y = {} ⟹ x ∈ M ⟹ y ∈ M ⟹ f (x ∪ y) = f x + f y" by (auto simp add: additive_def) lemma increasingD: "increasing M f ⟹ x ⊆ y ⟹ x∈M ⟹ y∈M ⟹ f x ≤ f y" by (auto simp add: increasing_def) lemma countably_additiveI[case_names countably]: "(⋀A. range A ⊆ M ⟹ disjoint_family A ⟹ (⋃i. A i) ∈ M ⟹ (∑i. f (A i)) = f (⋃i. A i)) ⟹ countably_additive M f" by (simp add: countably_additive_def) lemma (in ring_of_sets) disjointed_additive: assumes f: "positive M f" "additive M f" and A: "range A ⊆ M" "incseq A" shows "(∑i≤n. f (disjointed A i)) = f (A n)" proof (induct n) case (Suc n) then have "(∑i≤Suc n. f (disjointed A i)) = f (A n) + f (disjointed A (Suc n))" by simp also have "… = f (A n ∪ disjointed A (Suc n))" using A by (subst f(2)[THEN additiveD]) (auto simp: disjointed_mono) also have "A n ∪ disjointed A (Suc n) = A (Suc n)" using ‹incseq A› by (auto dest: incseq_SucD simp: disjointed_mono) finally show ?case . qed simp lemma (in ring_of_sets) additive_sum: fixes A:: "'i ⇒ 'a set" assumes f: "positive M f" and ad: "additive M f" and "finite S" and A: "A`S ⊆ M" and disj: "disjoint_family_on A S" shows "(∑i∈S. f (A i)) = f (⋃i∈S. A i)" using ‹finite S› disj A proof induct case empty show ?case using f by (simp add: positive_def) next case (insert s S) then have "A s ∩ (⋃i∈S. A i) = {}" by (auto simp add: disjoint_family_on_def neq_iff) moreover have "A s ∈ M" using insert by blast moreover have "(⋃i∈S. A i) ∈ M" using insert ‹finite S› by auto ultimately have "f (A s ∪ (⋃i∈S. A i)) = f (A s) + f(⋃i∈S. A i)" using ad UNION_in_sets A by (auto simp add: additive_def) with insert show ?case using ad disjoint_family_on_mono[of S "insert s S" A] by (auto simp add: additive_def subset_insertI) qed lemma (in ring_of_sets) additive_increasing: fixes f :: "'a set ⇒ ennreal" assumes posf: "positive M f" and addf: "additive M f" shows "increasing M f" proof (auto simp add: increasing_def) fix x y assume xy: "x ∈ M" "y ∈ M" "x ⊆ y" then have "y - x ∈ M" by auto then have "f x + 0 ≤ f x + f (y-x)" by (intro add_left_mono zero_le) also have "... = f (x ∪ (y-x))" using addf by (auto simp add: additive_def) (metis Diff_disjoint Un_Diff_cancel Diff xy(1,2)) also have "... = f y" by (metis Un_Diff_cancel Un_absorb1 xy(3)) finally show "f x ≤ f y" by simp qed lemma (in ring_of_sets) subadditive: fixes f :: "'a set ⇒ ennreal" assumes f: "positive M f" "additive M f" and A: "A`S ⊆ M" and S: "finite S" shows "f (⋃i∈S. A i) ≤ (∑i∈S. f (A i))" using S A proof (induct S) case empty thus ?case using f by (auto simp: positive_def) next case (insert x F) hence in_M: "A x ∈ M" "(⋃i∈F. A i) ∈ M" "(⋃i∈F. A i) - A x ∈ M" using A by force+ have subs: "(⋃i∈F. A i) - A x ⊆ (⋃i∈F. A i)" by auto have "(⋃i∈(insert x F). A i) = A x ∪ ((⋃i∈F. A i) - A x)" by auto hence "f (⋃i∈(insert x F). A i) = f (A x ∪ ((⋃i∈F. A i) - A x))" by simp also have "… = f (A x) + f ((⋃i∈F. A i) - A x)" using f(2) by (rule additiveD) (insert in_M, auto) also have "… ≤ f (A x) + f (⋃i∈F. A i)" using additive_increasing[OF f] in_M subs by (auto simp: increasing_def intro: add_left_mono) also have "… ≤ f (A x) + (∑i∈F. f (A i))" using insert by (auto intro: add_left_mono) finally show "f (⋃i∈(insert x F). A i) ≤ (∑i∈(insert x F). f (A i))" using insert by simp qed lemma (in ring_of_sets) countably_additive_additive: fixes f :: "'a set ⇒ ennreal" assumes posf: "positive M f" and ca: "countably_additive M f" shows "additive M f" proof (auto simp add: additive_def) fix x y assume x: "x ∈ M" and y: "y ∈ M" and "x ∩ y = {}" hence "disjoint_family (binaryset x y)" by (auto simp add: disjoint_family_on_def binaryset_def) hence "range (binaryset x y) ⊆ M ⟶ (⋃i. binaryset x y i) ∈ M ⟶ f (⋃i. binaryset x y i) = (∑ n. f (binaryset x y n))" using ca by (simp add: countably_additive_def) hence "{x,y,{}} ⊆ M ⟶ x ∪ y ∈ M ⟶ f (x ∪ y) = (∑n. f (binaryset x y n))" by (simp add: range_binaryset_eq UN_binaryset_eq) thus "f (x ∪ y) = f x + f y" using posf x y by (auto simp add: Un suminf_binaryset_eq positive_def) qed lemma (in algebra) increasing_additive_bound: fixes A:: "nat ⇒ 'a set" and f :: "'a set ⇒ ennreal" assumes f: "positive M f" and ad: "additive M f" and inc: "increasing M f" and A: "range A ⊆ M" and disj: "disjoint_family A" shows "(∑i. f (A i)) ≤ f Ω" proof (safe intro!: suminf_le_const) fix N note disj_N = disjoint_family_on_mono[OF _ disj, of "{..<N}"] have "(∑i<N. f (A i)) = f (⋃i∈{..<N}. A i)" using A by (intro additive_sum [OF f ad _ _]) (auto simp: disj_N) also have "... ≤ f Ω" using space_closed A by (intro increasingD[OF inc] finite_UN) auto finally show "(∑i<N. f (A i)) ≤ f Ω" by simp qed (insert f A, auto simp: positive_def) lemma (in ring_of_sets) countably_additiveI_finite: fixes μ :: "'a set ⇒ ennreal" assumes "finite Ω" "positive M μ" "additive M μ" shows "countably_additive M μ" proof (rule countably_additiveI) fix F :: "nat ⇒ 'a set" assume F: "range F ⊆ M" "(⋃i. F i) ∈ M" and disj: "disjoint_family F" have "∀i∈{i. F i ≠ {}}. ∃x. x ∈ F i" by auto from bchoice[OF this] obtain f where f: "⋀i. F i ≠ {} ⟹ f i ∈ F i" by auto have inj_f: "inj_on f {i. F i ≠ {}}" proof (rule inj_onI, simp) fix i j a b assume *: "f i = f j" "F i ≠ {}" "F j ≠ {}" then have "f i ∈ F i" "f j ∈ F j" using f by force+ with disj * show "i = j" by (auto simp: disjoint_family_on_def) qed have "finite (⋃i. F i)" by (metis F(2) assms(1) infinite_super sets_into_space) have F_subset: "{i. μ (F i) ≠ 0} ⊆ {i. F i ≠ {}}" by (auto simp: positiveD_empty[OF ‹positive M μ›]) moreover have fin_not_empty: "finite {i. F i ≠ {}}" proof (rule finite_imageD) from f have "f`{i. F i ≠ {}} ⊆ (⋃i. F i)" by auto then show "finite (f`{i. F i ≠ {}})" by (rule finite_subset) fact qed fact ultimately have fin_not_0: "finite {i. μ (F i) ≠ 0}" by (rule finite_subset) have disj_not_empty: "disjoint_family_on F {i. F i ≠ {}}" using disj by (auto simp: disjoint_family_on_def) from fin_not_0 have "(∑i. μ (F i)) = (∑i | μ (F i) ≠ 0. μ (F i))" by (rule suminf_finite) auto also have "… = (∑i | F i ≠ {}. μ (F i))" using fin_not_empty F_subset by (rule sum.mono_neutral_left) auto also have "… = μ (⋃i∈{i. F i ≠ {}}. F i)" using ‹positive M μ› ‹additive M μ› fin_not_empty disj_not_empty F by (intro additive_sum) auto also have "… = μ (⋃i. F i)" by (rule arg_cong[where f=μ]) auto finally show "(∑i. μ (F i)) = μ (⋃i. F i)" . qed lemma (in ring_of_sets) countably_additive_iff_continuous_from_below: fixes f :: "'a set ⇒ ennreal" assumes f: "positive M f" "additive M f" shows "countably_additive M f ⟷ (∀A. range A ⊆ M ⟶ incseq A ⟶ (⋃i. A i) ∈ M ⟶ (λi. f (A i)) ⇢ f (⋃i. A i))" unfolding countably_additive_def proof safe assume count_sum: "∀A. range A ⊆ M ⟶ disjoint_family A ⟶ ⋃(A ` UNIV) ∈ M ⟶ (∑i. f (A i)) = f (⋃(A ` UNIV))" fix A :: "nat ⇒ 'a set" assume A: "range A ⊆ M" "incseq A" "(⋃i. A i) ∈ M" then have dA: "range (disjointed A) ⊆ M" by (auto simp: range_disjointed_sets) with count_sum[THEN spec, of "disjointed A"] A(3) have f_UN: "(∑i. f (disjointed A i)) = f (⋃i. A i)" by (auto simp: UN_disjointed_eq disjoint_family_disjointed) moreover have "(λn. (∑i<n. f (disjointed A i))) ⇢ (∑i. f (disjointed A i))" using f(1)[unfolded positive_def] dA by (auto intro!: summable_LIMSEQ) from LIMSEQ_Suc[OF this] have "(λn. (∑i≤n. f (disjointed A i))) ⇢ (∑i. f (disjointed A i))" unfolding lessThan_Suc_atMost . moreover have "⋀n. (∑i≤n. f (disjointed A i)) = f (A n)" using disjointed_additive[OF f A(1,2)] . ultimately show "(λi. f (A i)) ⇢ f (⋃i. A i)" by simp next assume cont: "∀A. range A ⊆ M ⟶ incseq A ⟶ (⋃i. A i) ∈ M ⟶ (λi. f (A i)) ⇢ f (⋃i. A i)" fix A :: "nat ⇒ 'a set" assume A: "range A ⊆ M" "disjoint_family A" "(⋃i. A i) ∈ M" have *: "(⋃n. (⋃i<n. A i)) = (⋃i. A i)" by auto have "(λn. f (⋃i<n. A i)) ⇢ f (⋃i. A i)" proof (unfold *[symmetric], intro cont[rule_format]) show "range (λi. ⋃i<i. A i) ⊆ M" "(⋃i. ⋃i<i. A i) ∈ M" using A * by auto qed (force intro!: incseq_SucI) moreover have "⋀n. f (⋃i<n. A i) = (∑i<n. f (A i))" using A by (intro additive_sum[OF f, of _ A, symmetric]) (auto intro: disjoint_family_on_mono[where B=UNIV]) ultimately have "(λi. f (A i)) sums f (⋃i. A i)" unfolding sums_def by simp from sums_unique[OF this] show "(∑i. f (A i)) = f (⋃i. A i)" by simp qed lemma (in ring_of_sets) continuous_from_above_iff_empty_continuous: fixes f :: "'a set ⇒ ennreal" assumes f: "positive M f" "additive M f" shows "(∀A. range A ⊆ M ⟶ decseq A ⟶ (⋂i. A i) ∈ M ⟶ (∀i. f (A i) ≠ ∞) ⟶ (λi. f (A i)) ⇢ f (⋂i. A i)) ⟷ (∀A. range A ⊆ M ⟶ decseq A ⟶ (⋂i. A i) = {} ⟶ (∀i. f (A i) ≠ ∞) ⟶ (λi. f (A i)) ⇢ 0)" proof safe assume cont: "(∀A. range A ⊆ M ⟶ decseq A ⟶ (⋂i. A i) ∈ M ⟶ (∀i. f (A i) ≠ ∞) ⟶ (λi. f (A i)) ⇢ f (⋂i. A i))" fix A :: "nat ⇒ 'a set" assume A: "range A ⊆ M" "decseq A" "(⋂i. A i) = {}" "∀i. f (A i) ≠ ∞" with cont[THEN spec, of A] show "(λi. f (A i)) ⇢ 0" using ‹positive M f›[unfolded positive_def] by auto next assume cont: "∀A. range A ⊆ M ⟶ decseq A ⟶ (⋂i. A i) = {} ⟶ (∀i. f (A i) ≠ ∞) ⟶ (λi. f (A i)) ⇢ 0" fix A :: "nat ⇒ 'a set" assume A: "range A ⊆ M" "decseq A" "(⋂i. A i) ∈ M" "∀i. f (A i) ≠ ∞" have f_mono: "⋀a b. a ∈ M ⟹ b ∈ M ⟹ a ⊆ b ⟹ f a ≤ f b" using additive_increasing[OF f] unfolding increasing_def by simp have decseq_fA: "decseq (λi. f (A i))" using A by (auto simp: decseq_def intro!: f_mono) have decseq: "decseq (λi. A i - (⋂i. A i))" using A by (auto simp: decseq_def) then have decseq_f: "decseq (λi. f (A i - (⋂i. A i)))" using A unfolding decseq_def by (auto intro!: f_mono Diff) have "f (⋂x. A x) ≤ f (A 0)" using A by (auto intro!: f_mono) then have f_Int_fin: "f (⋂x. A x) ≠ ∞" using A by (auto simp: top_unique) { fix i have "f (A i - (⋂i. A i)) ≤ f (A i)" using A by (auto intro!: f_mono) then have "f (A i - (⋂i. A i)) ≠ ∞" using A by (auto simp: top_unique) } note f_fin = this have "(λi. f (A i - (⋂i. A i))) ⇢ 0" proof (intro cont[rule_format, OF _ decseq _ f_fin]) show "range (λi. A i - (⋂i. A i)) ⊆ M" "(⋂i. A i - (⋂i. A i)) = {}" using A by auto qed from INF_Lim[OF decseq_f this] have "(INF n. f (A n - (⋂i. A i))) = 0" . moreover have "(INF n. f (⋂i. A i)) = f (⋂i. A i)" by auto ultimately have "(INF n. f (A n - (⋂i. A i)) + f (⋂i. A i)) = 0 + f (⋂i. A i)" using A(4) f_fin f_Int_fin by (subst INF_ennreal_add_const) (auto simp: decseq_f) moreover { fix n have "f (A n - (⋂i. A i)) + f (⋂i. A i) = f ((A n - (⋂i. A i)) ∪ (⋂i. A i))" using A by (subst f(2)[THEN additiveD]) auto also have "(A n - (⋂i. A i)) ∪ (⋂i. A i) = A n" by auto finally have "f (A n - (⋂i. A i)) + f (⋂i. A i) = f (A n)" . } ultimately have "(INF n. f (A n)) = f (⋂i. A i)" by simp with LIMSEQ_INF[OF decseq_fA] show "(λi. f (A i)) ⇢ f (⋂i. A i)" by simp qed lemma (in ring_of_sets) empty_continuous_imp_continuous_from_below: fixes f :: "'a set ⇒ ennreal" assumes f: "positive M f" "additive M f" "∀A∈M. f A ≠ ∞" assumes cont: "∀A. range A ⊆ M ⟶ decseq A ⟶ (⋂i. A i) = {} ⟶ (λi. f (A i)) ⇢ 0" assumes A: "range A ⊆ M" "incseq A" "(⋃i. A i) ∈ M" shows "(λi. f (A i)) ⇢ f (⋃i. A i)" proof - from A have "(λi. f ((⋃i. A i) - A i)) ⇢ 0" by (intro cont[rule_format]) (auto simp: decseq_def incseq_def) moreover { fix i have "f ((⋃i. A i) - A i ∪ A i) = f ((⋃i. A i) - A i) + f (A i)" using A by (intro f(2)[THEN additiveD]) auto also have "((⋃i. A i) - A i) ∪ A i = (⋃i. A i)" by auto finally have "f ((⋃i. A i) - A i) = f (⋃i. A i) - f (A i)" using f(3)[rule_format, of "A i"] A by (auto simp: ennreal_add_diff_cancel subset_eq) } moreover have "∀⇩_{F}i in sequentially. f (A i) ≤ f (⋃i. A i)" using increasingD[OF additive_increasing[OF f(1, 2)], of "A _" "⋃i. A i"] A by (auto intro!: always_eventually simp: subset_eq) ultimately show "(λi. f (A i)) ⇢ f (⋃i. A i)" by (auto intro: ennreal_tendsto_const_minus) qed lemma (in ring_of_sets) empty_continuous_imp_countably_additive: fixes f :: "'a set ⇒ ennreal" assumes f: "positive M f" "additive M f" and fin: "∀A∈M. f A ≠ ∞" assumes cont: "⋀A. range A ⊆ M ⟹ decseq A ⟹ (⋂i. A i) = {} ⟹ (λi. f (A i)) ⇢ 0" shows "countably_additive M f" using countably_additive_iff_continuous_from_below[OF f] using empty_continuous_imp_continuous_from_below[OF f fin] cont by blast subsection✐‹tag unimportant› ‹Properties of \<^const>‹emeasure›› lemma emeasure_positive: "positive (sets M) (emeasure M)" by (cases M) (auto simp: sets_def emeasure_def Abs_measure_inverse measure_space_def) lemma emeasure_empty[simp, intro]: "emeasure M {} = 0" using emeasure_positive[of M] by (simp add: positive_def) lemma emeasure_single_in_space: "emeasure M {x} ≠ 0 ⟹ x ∈ space M" using emeasure_notin_sets[of "{x}" M] by (auto dest: sets.sets_into_space zero_less_iff_neq_zero[THEN iffD2]) lemma emeasure_countably_additive: "countably_additive (sets M) (emeasure M)" by (cases M) (auto simp: sets_def emeasure_def Abs_measure_inverse measure_space_def) lemma suminf_emeasure: "range A ⊆ sets M ⟹ disjoint_family A ⟹ (∑i. emeasure M (A i)) = emeasure M (⋃i. A i)" using sets.countable_UN[of A UNIV M] emeasure_countably_additive[of M] by (simp add: countably_additive_def) lemma sums_emeasure: "disjoint_family F ⟹ (⋀i. F i ∈ sets M) ⟹ (λi. emeasure M (F i)) sums emeasure M (⋃i. F i)" unfolding sums_iff by (intro conjI suminf_emeasure) auto lemma emeasure_additive: "additive (sets M) (emeasure M)" by (metis sets.countably_additive_additive emeasure_positive emeasure_countably_additive) lemma plus_emeasure: "a ∈ sets M ⟹ b ∈ sets M ⟹ a ∩ b = {} ⟹ emeasure M a + emeasure M b = emeasure M (a ∪ b)" using additiveD[OF emeasure_additive] .. lemma emeasure_Un: "A ∈ sets M ⟹ B ∈ sets M ⟹ emeasure M (A ∪ B) = emeasure M A + emeasure M (B - A)" using plus_emeasure[of A M "B - A"] by auto lemma emeasure_Un_Int: assumes "A ∈ sets M" "B ∈ sets M" shows "emeasure M A + emeasure M B = emeasure M (A ∪ B) + emeasure M (A ∩ B)" proof - have "A = (A-B) ∪ (A ∩ B)" by auto then have "emeasure M A = emeasure M (A-B) + emeasure M (A ∩ B)" by (metis Diff_Diff_Int Diff_disjoint assms plus_emeasure sets.Diff) moreover have "A ∪ B = (A-B) ∪ B" by auto then have "emeasure M (A ∪ B) = emeasure M (A-B) + emeasure M B" by (metis Diff_disjoint Int_commute assms plus_emeasure sets.Diff) ultimately show ?thesis by (metis add.assoc add.commute) qed lemma sum_emeasure: "F`I ⊆ sets M ⟹ disjoint_family_on F I ⟹ finite I ⟹ (∑i∈I. emeasure M (F i)) = emeasure M (⋃i∈I. F i)" by (metis sets.additive_sum emeasure_positive emeasure_additive) lemma emeasure_mono: "a ⊆ b ⟹ b ∈ sets M ⟹ emeasure M a ≤ emeasure M b" by (metis zero_le sets.additive_increasing emeasure_additive emeasure_notin_sets emeasure_positive increasingD) lemma emeasure_space: "emeasure M A ≤ emeasure M (space M)" by (metis emeasure_mono emeasure_notin_sets sets.sets_into_space sets.top zero_le) lemma emeasure_Diff: assumes finite: "emeasure M B ≠ ∞" and [measurable]: "A ∈ sets M" "B ∈ sets M" and "B ⊆ A" shows "emeasure M (A - B) = emeasure M A - emeasure M B" proof - have "(A - B) ∪ B = A" using ‹B ⊆ A› by auto then have "emeasure M A = emeasure M ((A - B) ∪ B)" by simp also have "… = emeasure M (A - B) + emeasure M B" by (subst plus_emeasure[symmetric]) auto finally show "emeasure M (A - B) = emeasure M A - emeasure M B" using finite by simp qed lemma emeasure_compl: "s ∈ sets M ⟹ emeasure M s ≠ ∞ ⟹ emeasure M (space M - s) = emeasure M (space M) - emeasure M s" by (rule emeasure_Diff) (auto dest: sets.sets_into_space) lemma Lim_emeasure_incseq: "range A ⊆ sets M ⟹ incseq A ⟹ (λi. (emeasure M (A i))) ⇢ emeasure M (⋃i. A i)" using emeasure_countably_additive by (auto simp add: sets.countably_additive_iff_continuous_from_below emeasure_positive emeasure_additive) lemma incseq_emeasure: assumes "range B ⊆ sets M" "incseq B" shows "incseq (λi. emeasure M (B i))" using assms by (auto simp: incseq_def intro!: emeasure_mono) lemma SUP_emeasure_incseq: assumes A: "range A ⊆ sets M" "incseq A" shows "(SUP n. emeasure M (A n)) = emeasure M (⋃i. A i)" using LIMSEQ_SUP[OF incseq_emeasure, OF A] Lim_emeasure_incseq[OF A] by (simp add: LIMSEQ_unique) lemma decseq_emeasure: assumes "range B ⊆ sets M" "decseq B" shows "decseq (λi. emeasure M (B i))" using assms by (auto simp: decseq_def intro!: emeasure_mono) lemma INF_emeasure_decseq: assumes A: "range A ⊆ sets M" and "decseq A" and finite: "⋀i. emeasure M (A i) ≠ ∞" shows "(INF n. emeasure M (A n)) = emeasure M (⋂i. A i)" proof - have le_MI: "emeasure M (⋂i. A i) ≤ emeasure M (A 0)" using A by (auto intro!: emeasure_mono) hence *: "emeasure M (⋂i. A i) ≠ ∞" using finite[of 0] by (auto simp: top_unique) have "emeasure M (A 0) - (INF n. emeasure M (A n)) = (SUP n. emeasure M (A 0) - emeasure M (A n))" by (simp add: ennreal_INF_const_minus) also have "… = (SUP n. emeasure M (A 0 - A n))" using A finite ‹decseq A›[unfolded decseq_def] by (subst emeasure_Diff) auto also have "… = emeasure M (⋃i. A 0 - A i)" proof (rule SUP_emeasure_incseq) show "range (λn. A 0 - A n) ⊆ sets M" using A by auto show "incseq (λn. A 0 - A n)" using ‹decseq A› by (auto simp add: incseq_def decseq_def) qed also have "… = emeasure M (A 0) - emeasure M (⋂i. A i)" using A finite * by (simp, subst emeasure_Diff) auto finally show ?thesis by (rule ennreal_minus_cancel[rotated 3]) (insert finite A, auto intro: INF_lower emeasure_mono) qed lemma INF_emeasure_decseq': assumes A: "⋀i. A i ∈ sets M" and "decseq A" and finite: "∃i. emeasure M (A i) ≠ ∞" shows "(INF n. emeasure M (A n)) = emeasure M (⋂i. A i)" proof - from finite obtain i where i: "emeasure M (A i) < ∞" by (auto simp: less_top) have fin: "i ≤ j ⟹ emeasure M (A j) < ∞" for j by (rule le_less_trans[OF emeasure_mono i]) (auto intro!: decseqD[OF ‹decseq A›] A) have "(INF n. emeasure M (A n)) = (INF n. emeasure M (A (n + i)))" proof (rule INF_eq) show "∃j∈UNIV. emeasure M (A (j + i)) ≤ emeasure M (A i')" for i' by (intro bexI[of _ i'] emeasure_mono decseqD[OF ‹decseq A›] A) auto qed auto also have "… = emeasure M (INF n. (A (n + i)))" using A ‹decseq A› fin by (intro INF_emeasure_decseq) (auto simp: decseq_def less_top) also have "(INF n. (A (n + i))) = (INF n. A n)" by (meson INF_eq UNIV_I assms(2) decseqD le_add1) finally show ?thesis . qed lemma emeasure_INT_decseq_subset: fixes F :: "nat ⇒ 'a set" assumes I: "I ≠ {}" and F: "⋀i j. i ∈ I ⟹ j ∈ I ⟹ i ≤ j ⟹ F j ⊆ F i" assumes F_sets[measurable]: "⋀i. i ∈ I ⟹ F i ∈ sets M" and fin: "⋀i. i ∈ I ⟹ emeasure M (F i) ≠ ∞" shows "emeasure M (⋂i∈I. F i) = (INF i∈I. emeasure M (F i))" proof cases assume "finite I" have "(⋂i∈I. F i) = F (Max I)" using I ‹finite I› by (intro antisym INF_lower INF_greatest F) auto moreover have "(INF i∈I. emeasure M (F i)) = emeasure M (F (Max I))" using I ‹finite I› by (intro antisym INF_lower INF_greatest F emeasure_mono) auto ultimately show ?thesis by simp next assume "infinite I" define L where "L n = (LEAST i. i ∈ I ∧ i ≥ n)" for n have L: "L n ∈ I ∧ n ≤ L n" for n unfolding L_def proof (rule LeastI_ex) show "∃x. x ∈ I ∧ n ≤ x" using ‹infinite I› finite_subset[of I "{..< n}"] by (rule_tac ccontr) (auto simp: not_le) qed have L_eq[simp]: "i ∈ I ⟹ L i = i" for i unfolding L_def by (intro Least_equality) auto have L_mono: "i ≤ j ⟹ L i ≤ L j" for i j using L[of j] unfolding L_def by (intro Least_le) (auto simp: L_def) have "emeasure M (⋂i. F (L i)) = (INF i. emeasure M (F (L i)))" proof (intro INF_emeasure_decseq[symmetric]) show "decseq (λi. F (L i))" using L by (intro antimonoI F L_mono) auto qed (insert L fin, auto) also have "… = (INF i∈I. emeasure M (F i))" proof (intro antisym INF_greatest) show "i ∈ I ⟹ (INF i. emeasure M (F (L i))) ≤ emeasure M (F i)" for i by (intro INF_lower2[of i]) auto qed (insert L, auto intro: INF_lower) also have "(⋂i. F (L i)) = (⋂i∈I. F i)" proof (intro antisym INF_greatest) show "i ∈ I ⟹ (⋂i. F (L i)) ⊆ F i" for i by (intro INF_lower2[of i]) auto qed (insert L, auto) finally show ?thesis . qed lemma Lim_emeasure_decseq: assumes A: "range A ⊆ sets M" "decseq A" and fin: "⋀i. emeasure M (A i) ≠ ∞" shows "(λi. emeasure M (A i)) ⇢ emeasure M (⋂i. A i)" using LIMSEQ_INF[OF decseq_emeasure, OF A] using INF_emeasure_decseq[OF A fin] by simp lemma emeasure_lfp'[consumes 1, case_names cont measurable]: assumes "P M" assumes cont: "sup_continuous F" assumes *: "⋀M A. P M ⟹ (⋀N. P N ⟹ Measurable.pred N A) ⟹ Measurable.pred M (F A)" shows "emeasure M {x∈space M. lfp F x} = (SUP i. emeasure M {x∈space M. (F ^^ i) (λx. False) x})" proof - have "emeasure M {x∈space M. lfp F x} = emeasure M (⋃i. {x∈space M. (F ^^ i) (λx. False) x})" using sup_continuous_lfp[OF cont] by (auto simp add: bot_fun_def intro!: arg_cong2[where f=emeasure]) moreover { fix i from ‹P M› have "{x∈space M. (F ^^ i) (λx. False) x} ∈ sets M" by (induct i arbitrary: M) (auto simp add: pred_def[symmetric] intro: *) } moreover have "incseq (λi. {x∈space M. (F ^^ i) (λx. False) x})" proof (rule incseq_SucI) fix i have "(F ^^ i) (λx. False) ≤ (F ^^ (Suc i)) (λx. False)" proof (induct i) case 0 show ?case by (simp add: le_fun_def) next case Suc thus ?case using monoD[OF sup_continuous_mono[OF cont] Suc] by auto qed then show "{x ∈ space M. (F ^^ i) (λx. False) x} ⊆ {x ∈ space M. (F ^^ Suc i) (λx. False) x}" by auto qed ultimately show ?thesis by (subst SUP_emeasure_incseq) auto qed lemma emeasure_lfp: assumes [simp]: "⋀s. sets (M s) = sets N" assumes cont: "sup_continuous F" "sup_continuous f" assumes meas: "⋀P. Measurable.pred N P ⟹ Measurable.pred N (F P)" assumes iter: "⋀P s. Measurable.pred N P ⟹ P ≤ lfp F ⟹ emeasure (M s) {x∈space N. F P x} = f (λs. emeasure (M s) {x∈space N. P x}) s" shows "emeasure (M s) {x∈space N. lfp F x} = lfp f s" proof (subst lfp_transfer_bounded[where α="λF s. emeasure (M s) {x∈space N. F x}" and g=f and f=F and P="Measurable.pred N", symmetric]) fix C assume "incseq C" "⋀i. Measurable.pred N (C i)" then show "(λs. emeasure (M s) {x ∈ space N. (SUP i. C i) x}) = (SUP i. (λs. emeasure (M s) {x ∈ space N. C i x}))" unfolding SUP_apply[abs_def] by (subst SUP_emeasure_incseq) (auto simp: mono_def fun_eq_iff intro!: arg_cong2[where f=emeasure]) qed (auto simp add: iter le_fun_def SUP_apply[abs_def] intro!: meas cont) lemma emeasure_subadditive_finite: "finite I ⟹ A ` I ⊆ sets M ⟹ emeasure M (⋃i∈I. A i) ≤ (∑i∈I. emeasure M (A i))" by (rule sets.subadditive[OF emeasure_positive emeasure_additive]) auto lemma emeasure_subadditive: "A ∈ sets M ⟹ B ∈ sets M ⟹ emeasure M (A ∪ B) ≤ emeasure M A + emeasure M B" using emeasure_subadditive_finite[of "{True, False}" "λTrue ⇒ A | False ⇒ B" M] by simp lemma emeasure_subadditive_countably: assumes "range f ⊆ sets M" shows "emeasure M (⋃i. f i) ≤ (∑i. emeasure M (f i))" proof - have "emeasure M (⋃i. f i) = emeasure M (⋃i. disjointed f i)" unfolding UN_disjointed_eq .. also have "… = (∑i. emeasure M (disjointed f i))" using sets.range_disjointed_sets[OF assms] suminf_emeasure[of "disjointed f"] by (simp add: disjoint_family_disjointed comp_def) also have "… ≤ (∑i. emeasure M (f i))" using sets.range_disjointed_sets[OF assms] assms by (auto intro!: suminf_le emeasure_mono disjointed_subset) finally show ?thesis . qed lemma emeasure_insert: assumes sets: "{x} ∈ sets M" "A ∈ sets M" and "x ∉ A" shows "emeasure M (insert x A) = emeasure M {x} + emeasure M A" proof - have "{x} ∩ A = {}" using ‹x ∉ A› by auto from plus_emeasure[OF sets this] show ?thesis by simp qed lemma emeasure_insert_ne: "A ≠ {} ⟹ {x} ∈ sets M ⟹ A ∈ sets M ⟹ x ∉ A ⟹ emeasure M (insert x A) = emeasure M {x} + emeasure M A" by (rule emeasure_insert) lemma emeasure_eq_sum_singleton: assumes "finite S" "⋀x. x ∈ S ⟹ {x} ∈ sets M" shows "emeasure M S = (∑x∈S. emeasure M {x})" using sum_emeasure[of "λx. {x}" S M] assms by (auto simp: disjoint_family_on_def subset_eq) lemma sum_emeasure_cover: assumes "finite S" and "A ∈ sets M" and br_in_M: "B ` S ⊆ sets M" assumes A: "A ⊆ (⋃i∈S. B i)" assumes disj: "disjoint_family_on B S" shows "emeasure M A = (∑i∈S. emeasure M (A ∩ (B i)))" proof - have "(∑i∈S. emeasure M (A ∩ (B i))) = emeasure M (⋃i∈S. A ∩ (B i))" proof (rule sum_emeasure) show "disjoint_family_on (λi. A ∩ B i) S" using ‹disjoint_family_on B S› unfolding disjoint_family_on_def by auto qed (insert assms, auto) also have "(⋃i∈S. A ∩ (B i)) = A" using A by auto finally show ?thesis by simp qed lemma emeasure_eq_0: "N ∈ sets M ⟹ emeasure M N = 0 ⟹ K ⊆ N ⟹ emeasure M K = 0" by (metis emeasure_mono order_eq_iff zero_le) lemma emeasure_UN_eq_0: assumes "⋀i::nat. emeasure M (N i) = 0" and "range N ⊆ sets M" shows "emeasure M (⋃i. N i) = 0" proof - have "emeasure M (⋃i. N i) ≤ 0" using emeasure_subadditive_countably[OF assms(2)] assms(1) by simp then show ?thesis by (auto intro: antisym zero_le) qed lemma measure_eqI_finite: assumes [simp]: "sets M = Pow A" "sets N = Pow A" and "finite A" assumes eq: "⋀a. a ∈ A ⟹ emeasure M {a} = emeasure N {a}" shows "M = N" proof (rule measure_eqI) fix X assume "X ∈ sets M" then have X: "X ⊆ A" by auto then have "emeasure M X = (∑a∈X. emeasure M {a})" using ‹finite A› by (subst emeasure_eq_sum_singleton) (auto dest: finite_subset) also have "… = (∑a∈X. emeasure N {a})" using X eq by (auto intro!: sum.cong) also have "… = emeasure N X" using X ‹finite A› by (subst emeasure_eq_sum_singleton) (auto dest: finite_subset) finally show "emeasure M X = emeasure N X" . qed simp lemma measure_eqI_generator_eq: fixes M N :: "'a measure" and E :: "'a set set" and A :: "nat ⇒ 'a set" assumes "Int_stable E" "E ⊆ Pow Ω" and eq: "⋀X. X ∈ E ⟹ emeasure M X = emeasure N X" and M: "sets M = sigma_sets Ω E" and N: "sets N = sigma_sets Ω E" and A: "range A ⊆ E" "(⋃i. A i) = Ω" "⋀i. emeasure M (A i) ≠ ∞" shows "M = N" proof - let ?μ = "emeasure M" and ?ν = "emeasure N" interpret S: sigma_algebra Ω "sigma_sets Ω E" by (rule sigma_algebra_sigma_sets) fact have "space M = Ω" using sets.top[of M] sets.space_closed[of M] S.top S.space_closed ‹sets M = sigma_sets Ω E› by blast { fix F D assume "F ∈ E" and "?μ F ≠ ∞" then have [intro]: "F ∈ sigma_sets Ω E" by auto have "?ν F ≠ ∞" using ‹?μ F ≠ ∞› ‹F ∈ E› eq by simp assume "D ∈ sets M" with ‹Int_stable E› ‹E ⊆ Pow Ω› have "emeasure M (F ∩ D) = emeasure N (F ∩ D)" unfolding M proof (induct rule: sigma_sets_induct_disjoint) case (basic A) then have "F ∩ A ∈ E" using ‹Int_stable E› ‹F ∈ E› by (auto simp: Int_stable_def) then show ?case using eq by auto next case empty then show ?case by simp next case (compl A) then have **: "F ∩ (Ω - A) = F - (F ∩ A)" and [intro]: "F ∩ A ∈ sigma_sets Ω E" using ‹F ∈ E› S.sets_into_space by (auto simp: M) have "?ν (F ∩ A) ≤ ?ν F" by (auto intro!: emeasure_mono simp: M N) then have "?ν (F ∩ A) ≠ ∞" using ‹?ν F ≠ ∞› by (auto simp: top_unique) have "?μ (F ∩ A) ≤ ?μ F" by (auto intro!: emeasure_mono simp: M N) then have "?μ (F ∩ A) ≠ ∞" using ‹?μ F ≠ ∞› by (auto simp: top_unique) then have "?μ (F ∩ (Ω - A)) = ?μ F - ?μ (F ∩ A)" unfolding ** using ‹F ∩ A ∈ sigma_sets Ω E› by (auto intro!: emeasure_Diff simp: M N) also have "… = ?ν F - ?ν (F ∩ A)" using eq ‹F ∈ E› compl by simp also have "… = ?ν (F ∩ (Ω - A))" unfolding ** using ‹F ∩ A ∈ sigma_sets Ω E› ‹?ν (F ∩ A) ≠ ∞› by (auto intro!: emeasure_Diff[symmetric] simp: M N) finally show ?case using ‹space M = Ω› by auto next case (union A) then have "?μ (⋃x. F ∩ A x) = ?ν (⋃x. F ∩ A x)" by (subst (1 2) suminf_emeasure[symmetric]) (auto simp: disjoint_family_on_def subset_eq M N) with A show ?case by auto qed } note * = this show "M = N" proof (rule measure_eqI) show "sets M = sets N" using M N by simp have [simp, intro]: "⋀i. A i ∈ sets M" using A(1) by (auto simp: subset_eq M) fix F assume "F ∈ sets M" let ?D = "disjointed (λi. F ∩ A i)" from ‹space M = Ω› have F_eq: "F = (⋃i. ?D i)" using ‹F ∈ sets M›[THEN sets.sets_into_space] A(2)[symmetric] by (auto simp: UN_disjointed_eq) have [simp, intro]: "⋀i. ?D i ∈ sets M" using sets.range_disjointed_sets[of "λi. F ∩ A i" M] ‹F ∈ sets M› by (auto simp: subset_eq) have "disjoint_family ?D" by (auto simp: disjoint_family_disjointed) moreover have "(∑i. emeasure M (?D i)) = (∑i. emeasure N (?D i))" proof (intro arg_cong[where f=suminf] ext) fix i have "A i ∩ ?D i = ?D i" by (auto simp: disjointed_def) then show "emeasure M (?D i) = emeasure N (?D i)" using *[of "A i" "?D i", OF _ A(3)] A(1) by auto qed ultimately show "emeasure M F = emeasure N F" by (simp add: image_subset_iff ‹sets M = sets N›[symmetric] F_eq[symmetric] suminf_emeasure) qed qed lemma space_empty: "space M = {} ⟹ M = count_space {}" by (rule measure_eqI) (simp_all add: space_empty_iff) lemma measure_eqI_generator_eq_countable: fixes M N :: "'a measure" and E :: "'a set set" and A :: "'a set set" assumes E: "Int_stable E" "E ⊆ Pow Ω" "⋀X. X ∈ E ⟹ emeasure M X = emeasure N X" and sets: "sets M = sigma_sets Ω E" "sets N = sigma_sets Ω E" and A: "A ⊆ E" "(⋃A) = Ω" "countable A" "⋀a. a ∈ A ⟹ emeasure M a ≠ ∞" shows "M = N" proof cases assume "Ω = {}" have *: "sigma_sets Ω E = sets (sigma Ω E)" using E(2) by simp have "space M = Ω" "space N = Ω" using sets E(2) unfolding * by (auto dest: sets_eq_imp_space_eq simp del: sets_measure_of) then show "M = N" unfolding ‹Ω = {}› by (auto dest: space_empty) next assume "Ω ≠ {}" with ‹⋃A = Ω› have "A ≠ {}" by auto from this ‹countable A› have rng: "range (from_nat_into A) = A" by (rule range_from_nat_into) show "M = N" proof (rule measure_eqI_generator_eq[OF E sets]) show "range (from_nat_into A) ⊆ E" unfolding rng using ‹A ⊆ E› . show "(⋃i. from_nat_into A i) = Ω" unfolding rng using ‹⋃A = Ω› . show "emeasure M (from_nat_into A i) ≠ ∞" for i using rng by (intro A) auto qed qed lemma measure_of_of_measure: "measure_of (space M) (sets M) (emeasure M) = M" proof (intro measure_eqI emeasure_measure_of_sigma) show "sigma_algebra (space M) (sets M)" .. show "positive (sets M) (emeasure M)" by (simp add: positive_def) show "countably_additive (sets M) (emeasure M)" by (simp add: emeasure_countably_additive) qed simp_all subsection ‹‹μ›-null sets› definition✐‹tag important› null_sets :: "'a measure ⇒ 'a set set" where "null_sets M = {N∈sets M. emeasure M N = 0}" lemma null_setsD1[dest]: "A ∈ null_sets M ⟹ emeasure M A = 0" by (simp add: null_sets_def) lemma null_setsD2[dest]: "A ∈ null_sets M ⟹ A ∈ sets M" unfolding null_sets_def by simp lemma null_setsI[intro]: "emeasure M A = 0 ⟹ A ∈ sets M ⟹ A ∈ null_sets M" unfolding null_sets_def by simp interpretation null_sets: ring_of_sets "space M" "null_sets M" for M proof (rule ring_of_setsI) show "null_sets M ⊆ Pow (space M)" using sets.sets_into_space by auto show "{} ∈ null_sets M" by auto fix A B assume null_sets: "A ∈ null_sets M" "B ∈ null_sets M" then have sets: "A ∈ sets M" "B ∈ sets M" by auto then have *: "emeasure M (A ∪ B) ≤ emeasure M A + emeasure M B" "emeasure M (A - B) ≤ emeasure M A" by (auto intro!: emeasure_subadditive emeasure_mono) then have "emeasure M B = 0" "emeasure M A = 0" using null_sets by auto with sets * show "A - B ∈ null_sets M" "A ∪ B ∈ null_sets M" by (auto intro!: antisym zero_le) qed lemma UN_from_nat_into: assumes I: "countable I" "I ≠ {}" shows "(⋃i∈I. N i) = (⋃i. N (from_nat_into I i))" proof - have "(⋃i∈I. N i) = ⋃(N ` range (from_nat_into I))" using I by simp also have "… = (⋃i. (N ∘ from_nat_into I) i)" by simp finally show ?thesis by simp qed lemma null_sets_UN': assumes "countable I" assumes "⋀i. i ∈ I ⟹ N i ∈ null_sets M" shows "(⋃i∈I. N i) ∈ null_sets M" proof cases assume "I = {}" then show ?thesis by simp next assume "I ≠ {}" show ?thesis proof (intro conjI CollectI null_setsI) show "(⋃i∈I. N i) ∈ sets M" using assms by (intro sets.countable_UN') auto have "emeasure M (⋃i∈I. N i) ≤ (∑n. emeasure M (N (from_nat_into I n)))" unfolding UN_from_nat_into[OF ‹countable I› ‹I ≠ {}›] using assms ‹I ≠ {}› by (intro emeasure_subadditive_countably) (auto intro: from_nat_into) also have "(λn. emeasure M (N (from_nat_into I n))) = (λ_. 0)" using assms ‹I ≠ {}› by (auto intro: from_nat_into) finally show "emeasure M (⋃i∈I. N i) = 0" by (intro antisym zero_le) simp qed qed lemma null_sets_UN[intro]: "(⋀i::'i::countable. N i ∈ null_sets M) ⟹ (⋃i. N i) ∈ null_sets M" by (rule null_sets_UN') auto lemma null_set_Int1: assumes "B ∈ null_sets M" "A ∈ sets M" shows "A ∩ B ∈ null_sets M" proof (intro CollectI conjI null_setsI) show "emeasure M (A ∩ B) = 0" using assms by (intro emeasure_eq_0[of B _ "A ∩ B"]) auto qed (insert assms, auto) lemma null_set_Int2: assumes "B ∈ null_sets M" "A ∈ sets M" shows "B ∩ A ∈ null_sets M" using assms by (subst Int_commute) (rule null_set_Int1) lemma emeasure_Diff_null_set: assumes "B ∈ null_sets M" "A ∈ sets M" shows "emeasure M (A - B) = emeasure M A" proof - have *: "A - B = (A - (A ∩ B))" by auto have "A ∩ B ∈ null_sets M" using assms by (rule null_set_Int1) then show ?thesis unfolding * using assms by (subst emeasure_Diff) auto qed lemma null_set_Diff: assumes "B ∈ null_sets M" "A ∈ sets M" shows "B - A ∈ null_sets M" proof (intro CollectI conjI null_setsI) show "emeasure M (B - A) = 0" using assms by (intro emeasure_eq_0[of B _ "B - A"]) auto qed (insert assms, auto) lemma emeasure_Un_null_set: assumes "A ∈ sets M" "B ∈ null_sets M" shows "emeasure M (A ∪ B) = emeasure M A" proof - have *: "A ∪ B = A ∪ (B - A)" by auto have "B - A ∈ null_sets M" using assms(2,1) by (rule null_set_Diff) then show ?thesis unfolding * using assms by (subst plus_emeasure[symmetric]) auto qed lemma emeasure_Un': assumes "A ∈ sets M" "B ∈ sets M" "A ∩ B ∈ null_sets M" shows "emeasure M (A ∪ B) = emeasure M A + emeasure M B" proof - have "A ∪ B = A ∪ (B - A ∩ B)" by blast also have "emeasure M … = emeasure M A + emeasure M (B - A ∩ B)" using assms by (subst plus_emeasure) auto also have "emeasure M (B - A ∩ B) = emeasure M B" using assms by (intro emeasure_Diff_null_set) auto finally show ?thesis . qed subsection ‹The almost everywhere filter (i.e.\ quantifier)› definition✐‹tag important› ae_filter :: "'a measure ⇒ 'a filter" where "ae_filter M = (INF N∈null_sets M. principal (space M - N))" abbreviation almost_everywhere :: "'a measure ⇒ ('a ⇒ bool) ⇒ bool" where "almost_everywhere M P ≡ eventually P (ae_filter M)" syntax "_almost_everywhere" :: "pttrn ⇒ 'a ⇒ bool ⇒ bool" ("AE _ in _. _" [0,0,10] 10) translations "AE x in M. P" ⇌ "CONST almost_everywhere M (λx. P)" abbreviation "set_almost_everywhere A M P ≡ AE x in M. x ∈ A ⟶ P x" syntax "_set_almost_everywhere" :: "pttrn ⇒ 'a set ⇒ 'a ⇒ bool ⇒ bool" ("AE _∈_ in _./ _" [0,0,0,10] 10) translations "AE x∈A in M. P" ⇌ "CONST set_almost_everywhere A M (λx. P)" lemma eventually_ae_filter: "eventually P (ae_filter M) ⟷ (∃N∈null_sets M. {x ∈ space M. ¬ P x} ⊆ N)" unfolding ae_filter_def by (subst eventually_INF_base) (auto simp: eventually_principal subset_eq) lemma AE_I': "N ∈ null_sets M ⟹ {x∈space M. ¬ P x} ⊆ N ⟹ (AE x in M. P x)" unfolding eventually_ae_filter by auto lemma AE_iff_null: assumes "{x∈space M. ¬ P x} ∈ sets M" (is "?P ∈ sets M") shows "(AE x in M. P x) ⟷ {x∈space M. ¬ P x} ∈ null_sets M" proof assume "AE x in M. P x" then obtain N where N: "N ∈ sets M" "?P ⊆ N" "emeasure M N = 0" unfolding eventually_ae_filter by auto have "emeasure M ?P ≤ emeasure M N" using assms N(1,2) by (auto intro: emeasure_mono) then have "emeasure M ?P = 0" unfolding ‹emeasure M N = 0› by auto then show "?P ∈ null_sets M" using assms by auto next assume "?P ∈ null_sets M" with assms show "AE x in M. P x" by (auto intro: AE_I') qed lemma AE_iff_null_sets: "N ∈ sets M ⟹ N ∈ null_sets M ⟷ (AE x in M. x ∉ N)" using Int_absorb1[OF sets.sets_into_space, of N M] by (subst AE_iff_null) (auto simp: Int_def[symmetric]) lemma AE_not_in: "N ∈ null_sets M ⟹ AE x in M. x ∉ N" by (metis AE_iff_null_sets null_setsD2) lemma AE_iff_measurable: "N ∈ sets M ⟹ {x∈space M. ¬ P x} = N ⟹ (AE x in M. P x) ⟷ emeasure M N = 0" using AE_iff_null[of _ P] by auto lemma AE_E[consumes 1]: assumes "AE x in M. P x" obtains N where "{x ∈ space M. ¬ P x} ⊆ N" "emeasure M N = 0" "N ∈ sets M" using assms unfolding eventually_ae_filter by auto lemma AE_E2: assumes "AE x in M. P x" "{x∈space M. P x} ∈ sets M" shows "emeasure M {x∈space M. ¬ P x} = 0" (is "emeasure M ?P = 0") proof - have "{x∈space M. ¬ P x} = space M - {x∈space M. P x}" by auto with AE_iff_null[of M P] assms show ?thesis by auto qed lemma AE_E3: assumes "AE x in M. P x" obtains N where "⋀x. x ∈ space M - N ⟹ P x" "N ∈ null_sets M" using assms unfolding eventually_ae_filter by auto lemma AE_I: assumes "{x ∈ space M. ¬ P x} ⊆ N" "emeasure M N = 0" "N ∈ sets M" shows "AE x in M. P x" using assms unfolding eventually_ae_filter by auto lemma AE_mp[elim!]: assumes AE_P: "AE x in M. P x" and AE_imp: "AE x in M. P x ⟶ Q x" shows "AE x in M. Q x" proof - from AE_P obtain A where P: "{x∈space M. ¬ P x} ⊆ A" and A: "A ∈ sets M" "emeasure M A = 0" by (auto elim!: AE_E) from AE_imp obtain B where imp: "{x∈space M. P x ∧ ¬ Q x} ⊆ B" and B: "B ∈ sets M" "emeasure M B = 0" by (auto elim!: AE_E) show ?thesis proof (intro AE_I) have "emeasure M (A ∪ B) ≤ 0" using emeasure_subadditive[of A M B] A B by auto then show "A ∪ B ∈ sets M" "emeasure M (A ∪ B) = 0" using A B by auto show "{x∈space M. ¬ Q x} ⊆ A ∪ B" using P imp by auto qed qed text ‹The next lemma is convenient to combine with a lemma whose conclusion is of the form ‹AE x in M. P x = Q x›: for such a lemma, there is no ‹[symmetric]› variant, but using ‹AE_symmetric[OF...]› will replace it.› (* depricated replace by laws about eventually *) lemma shows AE_iffI: "AE x in M. P x ⟹ AE x in M. P x ⟷ Q x ⟹ AE x in M. Q x" and AE_disjI1: "AE x in M. P x ⟹ AE x in M. P x ∨ Q x" and AE_disjI2: "AE x in M. Q x ⟹ AE x in M. P x ∨ Q x" and AE_conjI: "AE x in M. P x ⟹ AE x in M. Q x ⟹ AE x in M. P x ∧ Q x" and AE_conj_iff[simp]: "(AE x in M. P x ∧ Q x) ⟷ (AE x in M. P x) ∧ (AE x in M. Q x)" by auto lemma AE_symmetric: assumes "AE x in M. P x = Q x" shows "AE x in M. Q x = P x" using assms by auto lemma AE_impI: "(P ⟹ AE x in M. Q x) ⟹ AE x in M. P ⟶ Q x" by fastforce lemma AE_measure: assumes AE: "AE x in M. P x" and sets: "{x∈space M. P x} ∈ sets M" (is "?P ∈ sets M") shows "emeasure M {x∈space M. P x} = emeasure M (space M)" proof - from AE_E[OF AE] obtain N where N: "{x ∈ space M. ¬ P x} ⊆ N" "emeasure M N = 0" "N ∈ sets M" by auto with sets have "emeasure M (space M) ≤ emeasure M (?P ∪ N)" by (intro emeasure_mono) auto also have "… ≤ emeasure M ?P + emeasure M N" using sets N by (intro emeasure_subadditive) auto also have "… = emeasure M ?P" using N by simp finally show "emeasure M ?P = emeasure M (space M)" using emeasure_space[of M "?P"] by auto qed lemma AE_space: "AE x in M. x ∈ space M" by (rule AE_I[where N="{}"]) auto lemma AE_I2[simp, intro]: "(⋀x. x ∈ space M ⟹ P x) ⟹ AE x in M. P x" using AE_space by force lemma AE_Ball_mp: "∀x∈space M. P x ⟹ AE x in M. P x ⟶ Q x ⟹ AE x in M. Q x" by auto lemma AE_cong[cong]: "(⋀x. x ∈ space M ⟹ P x ⟷ Q x) ⟹ (AE x in M. P x) ⟷ (AE x in M. Q x)" by auto lemma AE_cong_simp: "M = N ⟹ (⋀x. x ∈ space N =simp=> P x = Q x) ⟹ (AE x in M. P x) ⟷ (AE x in N. Q x)" by (auto simp: simp_implies_def) lemma AE_all_countable: "(AE x in M. ∀i. P i x) ⟷ (∀i::'i::countable. AE x in M. P i x)" proof assume "∀i. AE x in M. P i x" from this[unfolded eventually_ae_filter Bex_def, THEN choice] obtain N where N: "⋀i. N i ∈ null_sets M" "⋀i. {x∈space M. ¬ P i x} ⊆ N i" by auto have "{x∈space M. ¬ (∀i. P i x)} ⊆ (⋃i. {x∈space M. ¬ P i x})" by auto also have "… ⊆ (⋃i. N i)" using N by auto finally have "{x∈space M. ¬ (∀i. P i x)} ⊆ (⋃i. N i)" . moreover from N have "(⋃i. N i) ∈ null_sets M" by (intro null_sets_UN) auto ultimately show "AE x in M. ∀i. P i x" unfolding eventually_ae_filter by auto qed auto lemma AE_ball_countable: assumes [intro]: "countable X" shows "(AE x in M. ∀y∈X. P x y) ⟷ (∀y∈X. AE x in M. P x y)" proof assume "∀y∈X. AE x in M. P x y" from this[unfolded eventually_ae_filter Bex_def, THEN bchoice] obtain N where N: "⋀y. y ∈ X ⟹ N y ∈ null_sets M" "⋀y. y ∈ X ⟹ {x∈space M. ¬ P x y} ⊆ N y" by auto have "{x∈space M. ¬ (∀y∈X. P x y)} ⊆ (⋃y∈X. {x∈space M. ¬ P x y})" by auto also have "… ⊆ (⋃y∈X. N y)" using N by auto finally have "{x∈space M. ¬ (∀y∈X. P x y)} ⊆ (⋃y∈X. N y)" . moreover from N have "(⋃y∈X. N y) ∈ null_sets M" by (intro null_sets_UN') auto ultimately show "AE x in M. ∀y∈X. P x y" unfolding eventually_ae_filter by auto qed auto lemma AE_ball_countable': "(⋀N. N ∈ I ⟹ AE x in M. P N x) ⟹ countable I ⟹ AE x in M. ∀N ∈ I. P N x" unfolding AE_ball_countable by simp lemma AE_pairwise: "countable F ⟹ pairwise (λA B. AE x in M. R x A B) F ⟷ (AE x in M. pairwise (R x) F)" unfolding pairwise_alt by (simp add: AE_ball_countable) lemma AE_discrete_difference: assumes X: "countable X" assumes null: "⋀x. x ∈ X ⟹ emeasure M {x} = 0" assumes sets: "⋀x. x ∈ X ⟹ {x} ∈ sets M" shows "AE x in M. x ∉ X" proof - have "(⋃x∈X. {x}) ∈ null_sets M" using assms by (intro null_sets_UN') auto from AE_not_in[OF this] show "AE x in M. x ∉ X" by auto qed lemma AE_finite_all: assumes f: "finite S" shows "(AE x in M. ∀i∈S. P i x) ⟷ (∀i∈S. AE x in M. P i x)" using f by induct auto lemma AE_finite_allI: assumes "finite S" shows "(⋀s. s ∈ S ⟹ AE x in M. Q s x) ⟹ AE x in M. ∀s∈S. Q s x" using AE_finite_all[OF ‹finite S›] by auto lemma emeasure_mono_AE: assumes imp: "AE x in M. x ∈ A ⟶ x ∈ B" and B: "B ∈ sets M" shows "emeasure M A ≤ emeasure M B" proof cases assume A: "A ∈ sets M" from imp obtain N where N: "{x∈space M. ¬ (x ∈ A ⟶ x ∈ B)} ⊆ N" "N ∈ null_sets M" by (auto simp: eventually_ae_filter) have "emeasure M A = emeasure M (A - N)" using N A by (subst emeasure_Diff_null_set) auto also have "emeasure M (A - N) ≤ emeasure M (B - N)" using N A B sets.sets_into_space by (auto intro!: emeasure_mono) also have "emeasure M (B - N) = emeasure M B" using N B by (subst emeasure_Diff_null_set) auto finally show ?thesis . qed (simp add: emeasure_notin_sets) lemma emeasure_eq_AE: assumes iff: "AE x in M. x ∈ A ⟷ x ∈ B" assumes A: "A ∈ sets M" and B: "B ∈ sets M" shows "emeasure M A = emeasure M B" using assms by (safe intro!: antisym emeasure_mono_AE) auto lemma emeasure_Collect_eq_AE: "AE x in M. P x ⟷ Q x ⟹ Measurable.pred M Q ⟹ Measurable.pred M P ⟹ emeasure M {x∈space M. P x} = emeasure M {x∈space M. Q x}" by (intro emeasure_eq_AE) auto lemma emeasure_eq_0_AE: "AE x in M. ¬ P x ⟹ emeasure M {x∈space M. P x} = 0" using AE_iff_measurable[OF _ refl, of M "λx. ¬ P x"] by (cases "{x∈space M. P x} ∈ sets M") (simp_all add: emeasure_notin_sets) lemma emeasure_0_AE: assumes "emeasure M (space M) = 0" shows "AE x in M. P x" using eventually_ae_filter assms by blast lemma emeasure_add_AE: assumes [measurable]: "A ∈ sets M" "B ∈ sets M" "C ∈ sets M" assumes 1: "AE x in M. x ∈ C ⟷ x ∈ A ∨ x ∈ B" assumes 2: "AE x in M. ¬ (x ∈ A ∧ x ∈ B)" shows "emeasure M C = emeasure M A + emeasure M B" proof - have "emeasure M C = emeasure M (A ∪ B)" by (rule emeasure_eq_AE) (insert 1, auto) also have "… = emeasure M A + emeasure M (B - A)" by (subst plus_emeasure) auto also have "emeasure M (B - A) = emeasure M B" by (rule emeasure_eq_AE) (insert 2, auto) finally show ?thesis . qed subsection